2022
DOI: 10.1186/s40543-022-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effects of seed invigoration treatments with precursor zinc salt and nano-sized zinc oxide (ZnO) particles on vegetative growth, grain yield, and quality characteristics of Zea mays

Abstract: Introduction The zinc micronutrient fertilizers have a critical impact on the grain productivity and quality attributes of maize. However, the low use-efficiency issues of the applied Zn-fertilizers are required to be addressed through the development of novel formulations and alternative application techniques. Objectives This field study investigates the comparative impact of seed invigoration (including seed priming and coating) treatments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Consistent with the results of previous studies that AM fungi help to absorb K and other nutrients [61], this study showed that AMF also promoted the uptake of K and the micronutrients Cu and Zn under Mo stress. Studies have shown that Zn is the specific activation ion of chloroplast carbonic anhydrase, which is a key point in controlling photosynthesis and provides the substrate for CO 2 fixation, thus promoting photosynthesis to a certain extent [62]. At the same time, Zn is a synthesis of chlorophyll precursor zinc porphyrin; thus, Zn is conducive to promoting chlorophyll synthesis, and chlorophyll plays a vital role in photosynthesis [63].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of previous studies that AM fungi help to absorb K and other nutrients [61], this study showed that AMF also promoted the uptake of K and the micronutrients Cu and Zn under Mo stress. Studies have shown that Zn is the specific activation ion of chloroplast carbonic anhydrase, which is a key point in controlling photosynthesis and provides the substrate for CO 2 fixation, thus promoting photosynthesis to a certain extent [62]. At the same time, Zn is a synthesis of chlorophyll precursor zinc porphyrin; thus, Zn is conducive to promoting chlorophyll synthesis, and chlorophyll plays a vital role in photosynthesis [63].…”
Section: Discussionmentioning
confidence: 99%
“…The FT-IR spectra were recorded from 4000 to 400 cm −1 wavenumbers on a FT-IR spectroscope (Cary 630, Agilent Technologies, Inc., Santa Clara, California, USA) equipped with a diamond attenuated total reflectance (ATR) assembly. The soil samples were analyzed by placing a known amount (5 mg) of the dried soil sample to obtain the peaks formed because of the interaction of the various soil components/compounds with the IR radiations in the % transmittance mode [ 24 ]. The % transmittance vs. wavenumbers (cm −1 ) data was obtained in csv format and the FTIR graphs were prepared after normalization procedure using Origin software (Origin version 9.0, Origin Lab Corp., Northampton, MA, USA) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The treatment with ZnO NPs increased yieldcontributing variables such as the number of seeds per cob and the 1000-grain weight. Coating seeds with ZnO NPs (40 mg L −1 ) significantly increased cob weight, starch, total soluble protein, and soil nutrient content (N, P, K, and Zn) [108].…”
Section: Effect Of Biosynthesized Zinc Oxide Nanoparticles (Zno Nps) ...mentioning
confidence: 99%